Discovery of Inhibitors of the Wnt and Hedgehog Signaling Pathways through the Catalytic Enantioselective Synthesis of an Iridoid‐Inspired Compound Collection1. Issue 47 (2nd October 2013) - Takayama, Hiroshi; Jia, Zhi‐Jun; Kremer, Lea; Bauer, Jonathan O.; Strohmann, Carsten; Ziegler, Slava; Antonchick, Andrey P.; Waldmann, Herbert
<x xml:space="preserve">Abstract</x> Cousins you can count on: An iridoid‐inspired compound collection was synthesized efficiently by the resolution of cyclic enones in an asymmetric cycloaddition with azomethine ylides. The collection contained novel potent inhibitors of the Wnt and Hedgehog signaling pathways.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>